THE APPLICATION OF DAVID EASTON SYSTEM THEORY IN THE POLICY-MAKING PROCESS OF USING FOREIGN WORKERS IN INDONESIA - Alianti, Trisma Yepa; Erawan , I Ketut Putra; Erviantono, Tedi (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
The policy on the use of foreign workers is an important concern in the context of economic and social development of a country like Indonesia. In this case, David Easton's System Theory provides a relevant foundation to analyze the related policy-making process. This article discusses the application of systems theory in the context of foreign labor policies in Indonesia. First, the article identifies inputs in the policy process, such as global pressures, labor needs, and political considerations. Then, through a conversion process, the government processes these inputs into concrete policies, including regulations regarding the acceptance and use of foreign workers. The output of this process is policy implementation, which is reflected in official decisions and practical steps taken by the government. In addition, this article also highlights the feedback mechanism that leads to policy evaluation and adjustment to accommodate changing external and internal conditions. By analyzing this process through the lens of David Easton's Systems Theory, this article provides a more in-depth understanding of the dynamics of foreign labor policymaking in Indonesia and its relevance in the context of the current global political and economic system.